Molecular characterization and therapeutic insights into biofilm positive Staphylococcus aureus isolated from subclinical mastitis in dairy buffaloes - Muhammad Ijaz; Muhammad Umar Javed; Arslan Ahmed (Revista Científica)
To investigate the prevalence and molecular characterization of biofilm-positive Staphylococcus aureus (S. aureus) isolates from a total of 384 quarter milk samples of buffaloes from 25 dairy farms in Faisalabad and Rawalpindi, Pakistan, a convenient sampling method was used. The sampling was performed per the National Mastitis Council, USA standard procedure. The study also highlighted the in vitro resistance pattern of biofilm- positive S. aureus and the role of commonly used NSAIDs and non-antibiotics in modulating the S. aureus associated antibiotic resistance. Based on the California mastitis test, the results depicted the prevalence of subclinical mastitis in buffaloes as 50.26% (193/384). In comparison, the prevalence of S. aureus was noted to be 38.02%, out of which 25.79% isolates were biofilm-positive based on the Congo red agar, microtitre plate test, and presence of the icaA gene. Phylogenetic analysis of the studied isolates showed a high similarity with Egyptian and Indian icaA-positive S. aureus isolates. The findings of antibiogram profiling showed that biofilm- positive isolates showed higher resistance against oxacillin (87.5%), followed by trimethoprim/ sulfamethoxazole (79.16%), gentamicin (75%), oxytetracycline (66.66%), and cefoxitin (62.5%), while fusidic acid and linezolid were among the least resistant antibiotics against biofilm-positive isolates. The combinations of resistant antibiotics with non-antibiotics were investigated using the well diffusion method and checkerboard assay. Antimicrobial effects of non-antibiotics against study isolates accessed through the well diffusion method showed higher inhibition zones for meloxicam followed by flunixin, ketoprofen, and ivermectin. The combinations of amoxicillin/meloxicam, cotrimoxazole/flunixin, cotrimoxazole/ ketoprofen, and gentamicin/ flunixin on well diffusion method, and cotrimoxazole/ flunixin, amoxicillin/ketoprofen and gentamicin/flunixin on checkerboard assay revealed synergistic interactions. The study concluded that biofilm-positive S. aureus is an emerging and prevailing cause of bubaline mastitis in dairy farms of the study area. The increasing antibiotic resistance of S. aureus can be modulated by combining the resistant antibiotics with NSAIDs, especially flunixin and ketoprofen, in in vitro trials. However, further research on in vivo trials needs to be conducted to evaluate the actual efficacy of these combinations in animal models.